2007
DOI: 10.1124/jpet.107.130062
|View full text |Cite
|
Sign up to set email alerts
|

[3H]A-585539 [(1S,4S)-2,2-Dimethyl-5-(6-phenylpyridazin-3-yl)-5-aza-2-azoniabicyclo[2.2.1]heptane], a Novel High-Affinity α7 Neuronal Nicotinic Receptor Agonist: Radioligand Binding Characterization to Rat and Human Brain

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 35 publications
6
33
0
Order By: Relevance
“…Because the desensitized state of the ␣7 nAChR exhibits a high affinity receptor state and this is the receptor form that is thought to be predominantly expressed during radioligand binding equilibrium conditions, good agreement for ␣7 ligands is expected for electrophysiologically determined IC 50 values and their affinity K i constants. Consistent with this view, we noted the IC 50 value of ϳ10 nM and K i value in the range of 0.4 to 8 nM for ABT-107 in this study, similar to data previously reported for other ␣7 nAChR ligands (Briggs and McKenna, 1998;Anderson et al, 2008).…”
supporting
confidence: 80%
“…Because the desensitized state of the ␣7 nAChR exhibits a high affinity receptor state and this is the receptor form that is thought to be predominantly expressed during radioligand binding equilibrium conditions, good agreement for ␣7 ligands is expected for electrophysiologically determined IC 50 values and their affinity K i constants. Consistent with this view, we noted the IC 50 value of ϳ10 nM and K i value in the range of 0.4 to 8 nM for ABT-107 in this study, similar to data previously reported for other ␣7 nAChR ligands (Briggs and McKenna, 1998;Anderson et al, 2008).…”
supporting
confidence: 80%
“…Pellets were thawed, homogenized in BSS-Tris buffer, pH 7.4, and diluted with buffer to approximately 100 (hippocampus) or 150 (frontal cortex) g protein/ aliquot. Binding conditions for the ␣7 nAChR antagonist [ 3 H]MLA and agonist [ 3 H]A-585539 were as described in detail elsewhere (Anderson et al, 2008). Membrane aliquots, ϳ7 nM [ 3 H]MLA (25 Ci/mmol) and 0.1% bovine serum albumin (BSA) in BSS-Tris buffer, pH 7.4, were incubated in quadruplicate in a final volume of 500 l for 60 min at 22°C.…”
Section: Methodsmentioning
confidence: 99%
“…,4S)-2,2-dimethyl-5-(6-phenylpyridazin-3-yl)-5-aza-2-azoniabicyclo[2.2.1]heptane (A-585539)] radioligand assay were used to determine ␣7 nAChR-binding densities as described previously (Anderson et al, 2008). Briefly, membrane-enriched fractions were prepared fresh from sacrificed male Sprague-Dawley rats, four saline-treated and four treated with ABT-107 (Charles River Laboratories, Inc., Wilmington, MA), 3 to 5 months old.…”
Section: Methodsmentioning
confidence: 99%
“…As described above, the most reliable labeling strategies are the use of a7 nAChR-specific radiolabeled ligands such as a-Btx, MLA, A-585539, CHIBA-1001, AZ11637326, A-582941, A-844606, NS14492, or NS14490 (Han et al, 2003;Tribollet et al, 2004;Anderson et al, 2008;Hashimoto et al, 2008;Toyohara et al, 2010;Ettrup et al, 2011;Maier et al, 2011;Rötering et al, 2014). An alternative approach is to detect a7 nAChR expression levels by measuring the levels of CHRNA7 mRNA, as was performed in monkey brain (Han et al, 2000) and in post mortem human brain (Breese et al, 1997).…”
Section: G Expression and Function Of A7 Nicotinic Acetylcholine Recmentioning
confidence: 99%